Return On Equity Analysis Reviewed From Debt To Equity Ratio And Total Asset Turnover (Study On The Textile And Garment Sectors Listed On The IDX For The 2020 - 2022 Period) - Melihatin, Melli; Yusnita, Rita Tri; Patimah, Titin (Universitas Dehasen Bengkulu, 2024)
The aim of this research is to determine the simultaneous or partial influence of the Debt To Equity Ratio (DER) variable and the Total Asset Turnover (TATO) variable on Return On Equity (ROE). The population used in this research is the annual financial reports of the Textile and Garment sector listed on the Indonesia Stock Exchange for the 2020-2022 period. The method used in this research is quantitative research with a causal associative approach. The sample selection used was purposive sampling. The sample used is the annual financial report of the textile and garment sector listed on the Indonesia Stock Exchange for the 2020-2022 period. The data source in this research is secondary data in the form of audited financial reports obtained from www.idx.co.id. The data analysis technique used is panel data regression with the help of EVIEWS 12. Based on the research results, it is concluded that the debt to equity ratio and total asset turnover simultaneously have a significant effect on return on equity. Partially, the debt to equity ratio has a significant effect on return on equity, while total asset turnover does not have a significant effect on return on equity.